Reduction of Delayed Homologous Recombination by Induction of Radioadaptive Response in RaDR-GFP Mice (Yonezawa Effect): An Old Player With a New Role - Cuihua Liu; Hirokazu Hirakawa; Kaoru Tanaka; Fazliana Mohd Saaya; Mitsuru Nenoi; Akira Fujimori; Bing Wang (SAGE Publishing, 2019)
Radiotherapy (RT) treats cancer effectively with high doses of ionizing radiation (IR) to killing cancer cells and shrinking tumors while bearing the risk of developing different side effects, including secondary cancer, which is most concerning for long-term health consequences. Genomic instability (GI) is a characteristic of most cancer cells, and IR-induced GI can manifest as delayed homologous recombination (HR). Radioadaptive response (RAR) is capable of reducing genotoxicity, cell transformation, mutation, and carcinogenesis, but the rational evidence describing its contributions to the reduction of radiation risk, in particular, carcinogenesis, remains fragmented. In this work, to investigate the impact of RAR on high-dose, IR-induced GI measured as delayed HR, the frequency of recombinant cells was comparatively studied under RAR-inducible and -uninducible conditions in the nucleated cells in hematopoietic tissues (bone marrow and spleen) using the Rosa26 Direct Repeat-green fluorescent protein (RaDR-GFP) homozygote mice. Results demonstrated that the frequency of recombinant cells was significantly lower in hematopoietic tissues under RAR-inducible condition. These findings suggest that reduction in delayed HR may be at least a part of the mechanisms underlying decreased carcinogenesis by RAR, and application of RAR would contribute to a more rigorous and scientifically grounded system of radiation protection in RT.